Study of peripheral dose from low-dose CT to adaptive radiotherapy of postoperative prostate cancer - Gan, Guanghui; Gong, Wei; Jia, Lecheng; Zhang, Wei; Wang, Shimei; Zhou, Juying; Jiang, Hua (Frontiers in Oncology, 2023)
The increasing use of computed tomography (CT) for adaptive radiotherapy (ART) has raised concerns about the peripheral radiation dose. This study investigates the feasibility of low-dose CT (LDCT) for postoperative prostate cancer ART to reduce the peripheral radiation dose, and evaluates the peripheral radiation dose of different imaging techniques and propose an image enhancement method based on deep-learning for LDCT.A linear accelerator integrated with a 16-slice fan-beamCT from UIH (United Imaging Healthcare, China) was utilized for prostate cancer ART.To reduce the tube current of CT for ART, LDCT was acquired. Peripheral doses of normal-dose CT (NDCT), LDCT, and mega-voltage computed tomography (MV-CT)were measured using a cylindrical Virtual Water TM phantom and an ion chamber. A deep learning model of LDCT for abdominal and pelvic based cycle-consistent generative adversarial network was employed to enhance the image quality of LDCT.Six postoperative prostate cancer patients were selected to evaluate the feasibility of low dose CT network restoration images (RCT) by the deep learning model for ART.The three aspects among NDCT, LDCT and RCT were compared: the Hounsfield Unit (HU) of the tissue, the Dice Similarity Coefficient (DSC) criterion of target and organ, and dose calculation differences.In terms of peripheral dose, the LDCT had a surface measurement point dose of approximately 1.85 mGy at the scanning field, while the doses of NDCT and MV-CT were higher at 22.85 mGy and 29.97 mGy, respectively. However, the image quality of LDCT was worse than NDCT. When compared to LDCT, the tissue HU value of RCT showed a significant improvement and was closer to that of NDCT. The DSC results for target CTV between RCT and NDCT were also impressive, reaching up to 94% for bladder and femoral heads, 98% for rectum, and 94% for the target organ.Additionally, the dose calculation differences for the ART plan based on LDCT and NDCT were all within 1%. Overall, these findings suggest that RCT can provide an effective alternative to NDCT and MV-CT with similar or better outcomes in HU values of tissue and organ damage. More testing is required before clinical application.